The Power and Promise of Group Work: Consumer Evaluation of Group Work Services in Gauteng, South Africa. (March 2017) - Rasool, Shahana; Ross, Eleanor
Purpose: In light of the limited research into consumers' experiences of group work services in South Africa, the study evaluated groups offered by a range of social service agencies in Gauteng to determine whether group interventions were perceived by users as developmental and empowering. Methods: Program evaluation was employed to evaluate 47 groups. Interviews were held with 222 persons to elicit their views on the groups in which they had participated. Results: Main findings were that organizations offered a rich diversity of groups, and membership was inclusive. Benefits of group work included gaining support and friendship, acquiring confidence, normalization of experiences through sharing with similar others, and learning new skills. Discussion: The groups reflected the diverse nature of South African society and the complexity of social issues. The groups were also perceived as highly empowering and developmental; however, the group work modality would seem to be underutilized by social workers.